AN INTELLIGENT TUTORING SYSTEM FOR LEARNING LISTENING TOEIC - Maria Asumpta Deny Kusumaningrum; Dewanti Ratna Pertiwi (Jurnal Berdaya Mandiri, 2021)
Nowadays, English proficiency to be one of the main requirements when someone continuous study and applies for a job. One of them is TOEIC (Test of English for International Communication). In SMK AAG Penerbangan Adisutjipto Yogyakarta, TOEIC is used to measure the students’ English proficiency. Various job vacancy advertisements require the applicants to achieve the standard TOEIC score. Therefore, preparation for taking English proficiency is needed to equip the students ready in facing the TOEIC test. Artificial intelligence (AI) technology can help to improve the students’ English proficiency. The use of AI becomes higher due to the advantages such as flexibility, accurateness, and direct feedback. This program applied AI technology to develop listening skill in TOEIC of the students in SMK AAG Penerbangan Adisutjipto Yogyakarta. The result from this community service is the students know the skills and strategies to do the listening skill in TOEIC test.